4D printing of soybean oil based shape memory polymer and its magnetic-sensitive composite via digital light processing. Issue 9 (13th June 2022) - Huang, Shu; Shan, Mingyuan; Zhang, Hang; Sheng, Jie; Zhou, Jianzhong; Cui, Chengyun; Wei, Jiean; Zhu, Wenlong; Lu, Jinzhong
ABSTRACT: With the awakening of environmental awareness and the development of 4D printing, the availability of renewable materials for 4D printing has become increasingly important. A kind of soybean oil-based photosensitive resins were prepared to fabricate SMP parts with acrylate epoxy soybean oil/isobornyl methacrylate/nano-Fe3 O4 (AESO/IBOMA/nano-Fe3 O4 ) networks. The effects of IBOMA and nano-Fe3 O4 concentration on mechanical and shape memory properties were systematically studied. The polymer can achieve high curing rate and printing accuracy. Break elongation of SMPs with 40 wt% IBOMA can up to 45.3% and tensile strength of SMPs with 60 wt% IBOMA can reach 44.3 MPa. The tensile-unload test results showed that the shape fixation rate and shape recovery rate of all formulations were higher than 90%. SMPs with 5 wt% Fe3 O4 can be actuated by a magnetic field and complete an 82.47% shape recovery process in 40 s. Graphical abstract: uf0001